1999
DOI: 10.1097/00006123-199901000-00041
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Chordoma: 40-Year Experience at a Major Cancer Center

Abstract: Our results suggest frequent recurrences in the majority of patients with chordomas. Radical resection is associated with a significantly longer disease-free interval, compared with subtotal removal of the tumor. Addition of radiation after subtotal resection improves the disease-free interval, although radiation therapy can generally be used only once. Based on these findings, we think that, whenever possible, radical resection should be the treatment of choice for sacral chordomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
240
5
16

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(271 citation statements)
references
References 15 publications
6
240
5
16
Order By: Relevance
“…Despite a similar trend of the surgical margin and previous surgery in conditional survival over time, an inadequate margin and previous surgery before referral continued to have a lower 5-year conditional survival, which is consistent with previous studies demonstrating that the surgical margin is an important predictor of survival [9,23,26,34,38,42]. The surgical margin is the main predictor factor for local control and disease-free survival [3,11,24,44]. Intralesional surgery resulted in a high recurrence rate.…”
Section: Figsupporting
confidence: 85%
See 3 more Smart Citations
“…Despite a similar trend of the surgical margin and previous surgery in conditional survival over time, an inadequate margin and previous surgery before referral continued to have a lower 5-year conditional survival, which is consistent with previous studies demonstrating that the surgical margin is an important predictor of survival [9,23,26,34,38,42]. The surgical margin is the main predictor factor for local control and disease-free survival [3,11,24,44]. Intralesional surgery resulted in a high recurrence rate.…”
Section: Figsupporting
confidence: 85%
“…Intralesional surgery resulted in a high recurrence rate. York et al [44] reported a 83% local recurrence rate of sacral chordoma after intralesional surgery. In the current study, all 16 patients who received primary surgery with an inadequate margin before referral developed local recurrence.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…5,8 Aggressive techniques of surgery allow a more total resection, but local recurrence rate is still high. [7][8][9] As many patients can survive despite the presence of symptoms, the use of CDFS time is potentially more valuable than the overall survival time. Therefore, we investigated the factors related with CDFS in sacral chordomas.…”
Section: Discussionmentioning
confidence: 99%